Forest and Land Fire: Indonesian Government's Homework on Communicating Environmental, Social and Legal Countermeasures in South Kalimantan - Waluyo, Bambang Dwi (Universitas Medan Area, 2024)
This research aims to elucidate the government's communication strategies on the forest and land fire catastrophe in South Kalimantan. By inquiring about the effectiveness of government communication regarding forest and land fires in South Kalimantan. By employing Ulber Silalahi's idea of government communication. The research methodology utilized in this work uses a qualitative approach, specifically of a descriptive type. The selected research methodology is descriptive qualitative, which entails investigating and understanding individual or group perspectives on human and social matters. The data collection methods utilized include interviews, examination of documents, and review of literature. There is little communication among the government, communities, and the private sector regarding government actions taken and implemented by the government bureaucracy concerning forest and land fires, which affect public, community, and commercial interests. To address and reduce the issue of forest and land fires, the Indonesian government and other relevant parties must adopt efficient policies and measures, including promoting agroforestry, education on fire prevention, enforcement of laws, and rehabilitation of degraded lands. Hence, it is crucial for the government to effectively disseminate diverse policies and measures aimed at preventing and resolving forest and land fires in South Kalimantan.